PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI BERBASIS APLIKASI CAPCUT TERHADAP KETERAMPILAN MENYIMAK SISWA KELAS IV SD NEGERI GAROT ACEH BESAR - Putro Davina Yasmin; Intan Safiah; Hasniyati (STKIP Subang, 2026)
The low listening skills of students are still a problem in Indonesian language learning, one of which is caused by the use of less varied learning media so that learning becomes less interesting and students have difficulty in understanding the content of the story. This study aims to determine the effect of using animated video media based on the CapCut application on the listening skills of fourth-grade students of SD Negeri Garot Aceh Besar. This study uses a quantitative approach with a quasi-experimental research type and a nonequivalent control group design. The study population was 70 students, with a sample of class IV-C as the experimental class and class IV-A as the control class. The data collection technique used a listening skills test given through a pretest and posttest. Data analysis was carried out using the N-Gain test, the Shapiro-Wilk normality test, and the Mann–Whitney U test. The results showed that the average listening skills of students in the experimental class increased from 25.57 to 80.71, while in the control class it increased from 23.43 to 46.57. The average N-Gain value of the experimental class was 0.74 with a high category and the control class was 0.30 with a medium category. The Mann–Whitney U test results showed a significance value of 0.001 < 0.05. Therefore, it can be concluded that the use of animated video media based on the CapCut application significantly impacted the listening skills of fourth-grade students at SD Negeri Garot, Aceh Besar. Animated video media based on the CapCut application can be an alternative Indonesian language learning medium to improve students' listening skills.